Export Diversification and Free Trade Agreements: The case of Peru - Vera, Eduardo (Latin American Journal of Trade Policy, 2023)
This research paper examines the effect of Free Trade Agreements (FTAs) on export diversification, focusing on Peruvian exports to five countries in the Asia Pacific region: China, Japan, South Korea, Thailand, and Singapore. By employing regression models with control variables, the study investigates the outcomes of FTAs on export patterns. The findings reveal that the FTA yielded two primary effects: general and lagged. The general effect of the FTA was observed in the case of Peruvian exports to China and Korea, whereby a greater variety of exported goods became available. On the other hand, the FTA signed with Japan, Thailand, and Singapore resulted in a gradual reduction in the concentration of exported items over time. These findings underscore the importance of comprehending the multifaceted impacts of FTAs on export diversification and emphasize the need for a nuanced understanding of how trade agreements influence export dynamics across diverse markets.